2020
DOI: 10.1016/j.resinv.2020.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Single-center experience of patients with interstitial lung diseases during the early days of the COVID-19 pandemic

Abstract: Introduction Patients with interstitial lung diseases (ILD) can be suspected to be at risk of experiencing a rapid flare-up due to COVID-19. However, no specific data are currently available for these patients. Methods We retrospectively analyzed a cohort of 401 patients with ILD and determined the proportion of patients hospitalized for proven severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and specific symptoms of COVID-19. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…An increase in the severe course of COVID‐19 was not reported in a retrospective study of 401 interstitial lung disease (ILD) patients receiving immunosuppressive therapy 78 . Contrary to this finding, patients with ILD in another study had an increased mortality (HR = 1.60, 95% CI = 1.17–2.18, p = 0.003) due to COVID‐19, especially those with obesity and poor respiratory function parameters, and the highest mortality has been reported in rheumatoid ILD and chronic hypersensitivity pneumonitis 79 .…”
Section: Discussionmentioning
confidence: 96%
“…An increase in the severe course of COVID‐19 was not reported in a retrospective study of 401 interstitial lung disease (ILD) patients receiving immunosuppressive therapy 78 . Contrary to this finding, patients with ILD in another study had an increased mortality (HR = 1.60, 95% CI = 1.17–2.18, p = 0.003) due to COVID‐19, especially those with obesity and poor respiratory function parameters, and the highest mortality has been reported in rheumatoid ILD and chronic hypersensitivity pneumonitis 79 .…”
Section: Discussionmentioning
confidence: 96%
“…However, unfortunately, there was very limited information on whether patients with ILD have a higher risk of COVID-19 than those without ILD. Two previous studies evaluated this issue [ 14 , 15 ]. However, since these studies were performed in single centres by indirectly comparing rates of COVID-19 with that of the general population, the results were inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas one study suggested that patients with ILD did not show the increased occurrence of severe COVID-19 [ 14 ], the other two studies showed that patients with ILD have more severe disease and poor prognosis than those without ILD [ 15 , 18 ]. In the former study [ 14 ], patients who were not hospitalised were not allowed to undergo specific PCR testing for SARS-CoV-2, which was solely reserved for the most severe cases during this pandemic. Thus, the number of overall ILD patients with COVID-19 could not be accurately evaluated, which limits the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients suffering from interstitial lung diseases (ILDs) could also be at an increased risk of experiencing a rapid eruption of the disease due to COVID-19. However, this hypothesis is based on causal diseases and the median age of a population, which is commonly above 60 years (Guiot et al, 2020). The clinical spectrum of COVID-19 contrasts widely, from asymptomatic disease to 'J18.9 Pneumonia, unspecified organism' and lifethreatening complications, which includes acute respiratory distress syndrome (ARDS), multisystem organ failure, and ultimately death (Berenguer et al, 2020).…”
Section: Complications Risk Factors and Mortality Rate Of Covid-19mentioning
confidence: 99%